Peningkatan Keterampilan Vokasional Membuat Souvenir Melalui Video Tutorial pada Murid dengan Disabilitas Rungu - Arisandi, Melita; Efrina, Elsa; Mahdi, Arisul; Muspita, Rila (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study was motivated by the difficulties faced by two 7th-grade students with hearing impairments A and K at SLB Negeri Pembina Palembang in crafting songket fabric scrap necklaces, as well as the limited use of instructional media for vocational skills. The study aimed to improve vocational skills in making these souvenirs through the use of video tutorials. A Classroom Action Research (CAR) method was employed, conducted over two cycles each comprising four meetings following the stages of planning, action, observation, and reflection. The research subjects consisted of the two students with hearing impairments and one classroom teacher. Data were collected through skills tests, observation, documentation, and reflection, and subsequently analyzed both quantitatively and qualitatively. The results indicated that the students' initial skills fell into the low category, with a mastery level of 0%. Following the intervention using video tutorials in Cycle I, achievement rose to 89% for Student A and 90% for Student K; performance improved further in Cycle II after adjustments were made based on reflections from Cycle I. Thus, video tutorials can enhance the vocational skills of students with hearing impairments in crafting necklaces from songket fabric scraps.